Evaluation of the Chemical Structure and Thermal Properties of Polyethylene Glycol (PEG)-Doped Polylactic Acid (PLA)/Multiwalled Carbon Nanotube (MWCNT) Composites - Rifa'i, Awaludin Fitroh; Kaavessina, Mujtahid; Distantina, Sperisa (Universitas Islam Indonesia, 2024)
This study aimed to investigate the chemical structure, thermal properties, and stability of polylactic acid (PLA) composites blended with multi-walled carbon nanotubes (MWCNTs) and polyethylene glycol (PEG). The composites were fabricated using a masterbatch blending method with two different molecular weights (Mw) of PEG. The masterbatch was initially prepared using solvent casting with chloroform as the solvent, followed by melt blending using an extruder. ATR-FTIR spectroscopy identified strong hydrogen bonds between the C=O groups of PLA and the –OH groups of PEG, as evidenced by the peak at 1748 cm¹. Differential Scanning Calorimetry (DSC) revealed that incorporating 14 wt% of PEG 10,000 into PLA/MWCNT composite significantly enhances the melting enthalpy (∆Hm) from 18.3 J/g to 24.6 J/g and the degree of crystallinity from 2% to 17.3%. The glass transition temperature (Tg) decreased with the addition of PEG, indicating increased chain mobility, while the melting temperature (Tm) remained relatively constant around 158 oC regardless of the PEG Mw. Despite the plasticizing effect of PEG, the thermal stability of the composites was maintained across different PEG Mw. Scanning Electron Microscope (SEM) images showed that MWCNTs were well dispersed within the blend, facilitated by ultrasonic stirring during preparation.